PENERAPAN MEDIA CROSSWORD PUZZLE DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INDONESIA DI KELAS II SD INPRES HARTACO INDAH : Penelitian Tindakan Kelas (PTK) - Sri Windy Sari; Munirah; Haslinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Implementation of Crossword Puzzle Media in Improving Indonesian Vocabulary Mastery in Grade II of SD Inpres Hartaco Indah. The main problem in this study is whether Crossword Puzzle media can improve Indonesian vocabulary mastery and how to implement it in grade II of SD Inpres Hartaco Indah. The purpose of this study is to describe the implementation of Crossword Puzzle media and efforts to improve Indonesian vocabulary mastery through Crossword Puzzle media. This type of research is classroom action research (Class Action Research) consisting of two cycles. The subjects in this study were 31 grade II students of SD Inpres Hartaco Indah.The results of the study showed an increase in every aspect of learning. Student involvement increased from 25.80% in cycle I to 29.03% in cycle II. The average vocabulary mastery score increased from 65.64 (sufficient category) to 85.16 (good category). Student learning completeness also increased from 48.39% (15 students) to 93.54% (29 students). Based on the results of the study above, it can be concluded that the mastery of Indonesian vocabulary of class II students of SD Inpres Hartaco Indah through the application of Crossword Puzzle media has increased.